Fatigue during a 5-km running time trial - Nummela, A. T.; Heath, K. A.; Paavolainen, L. M.; Lambert, M. I.; St. Clair Gibson, A.; Rusko, H. K.; Noakes, T. D. (International Journal of Sports Medicine, 2008)
This study investigated fatigue-induced changes in neuromuscular and stride characteristics during and immediately after the 5-km running time trial. Eighteen well-trained male distance runners performed a maximal 20-m sprint test and maximal voluntary contraction (MVC) in a leg press machine before and immediately after the 5-km running time trial. In all the tests the EMG of five lower limb muscles was measured. The results of the present study showed that muscle fatigue measured in maximal exercises like 20-m sprint and MVC are not related to the fatigue induced changes during the 5-km time trial. The fatigue in the 20-m sprint test was related to the maximal 20-m pretest velocity (r = 0.58, p < 0.05), but the velocity loss during the 5-km time trial was inversely related to 5-km performance (r = - 0.60, p < 0.05) and training volume (r = - 0.58, p < 0.05). It was concluded that the fatigue in 5-km running measured pre- and postexercise at maximal effort is more related to sprint performance rather than endurance performance, but the fatigue measured during the 5-km running is related to endurance performance and factors affecting pacing strategy.